2016
DOI: 10.3109/14992027.2016.1143980
|View full text |Cite
|
Sign up to set email alerts
|

D-methionine (D-met) significantly reduces kanamycin-induced ototoxicity in pigmented guinea pigs

Abstract: Objective: Test D-methionine (D-met) as an otoprotectant from kanamycin-induced ototoxicity and determine the lowest maximally protective D-met dose. Design: Auditory brainstem responses (ABR) were measured at 4, 8, 14, and 20 kHz at baseline and two, four, and six weeks after kanamycin and D-met administration initiation. ABR threshold shifts assessed auditory function. Following six-week ABR testing, animals were decapitated and cochleae collected for outer hair cell (OHC) quantification. Study sample: Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Pharmacological agents such as D-methionine have been shown to exhibit otoprotective benefits and therefore hold much potential. [17] Expression of certain neurotrophins in cochlear hair cells and neurotrophin receptors, selective tyrosine kinase receptor B (TrkB) and C (TrkC) and the low-affinity p75 receptor (a member of the tumour necrosis factor superfamily of receptors) in the spiral ganglion neurons, has been revealed. [18] Otoprotective agents can be aimed at protecting patients with normal auditory-vestibular function at the start of treatment, while neurotrophins can be an intervention that targets restoration.…”
Section: New Developments In the Prevention Of Ototoxicitymentioning
confidence: 99%
“…Pharmacological agents such as D-methionine have been shown to exhibit otoprotective benefits and therefore hold much potential. [17] Expression of certain neurotrophins in cochlear hair cells and neurotrophin receptors, selective tyrosine kinase receptor B (TrkB) and C (TrkC) and the low-affinity p75 receptor (a member of the tumour necrosis factor superfamily of receptors) in the spiral ganglion neurons, has been revealed. [18] Otoprotective agents can be aimed at protecting patients with normal auditory-vestibular function at the start of treatment, while neurotrophins can be an intervention that targets restoration.…”
Section: New Developments In the Prevention Of Ototoxicitymentioning
confidence: 99%
“…Extensive work in otoprotectant agents to reduce occurrence and severity of chemotherapy-induced hearing loss (and noise-induced hearing loss) has been underway for decades. 18 To compare across multiple clinical trial sites, and across multiple studies, outcomes must be uniform. If a safe and effective otoprotective agent could be identified, oncologists may be able to treat the cancer more aggressively without hearing loss consequences.…”
Section: Reviewmentioning
confidence: 99%
“…
transient spectroscopy, [ 16,17 ] transient photocurrent, [ 18 ] and thermally stimulated current. [ 19,20 ] It has been found that trapping is strongly dependent on the particular combination of D-A molecules and illumination conditions employed.
…”
mentioning
confidence: 99%
“…However, the important problem of the dependence of charge trapping on the content and concentration of D-A mixtures and on fi lm morphology has not yet been thoroughly investigated. Indeed, previous investigations have provided the density of gap states and/or trap site densities; [15][16][17][18][19][20] but, to our knowledge, a quantitative determination of the relationship between OPV performance and the density of trapped charges has not been reported.Using the experimental set up in Figure 1 , we illuminate the sample under investigation by a relatively intense, high-energy optical pump that generates excitons that subsequently dissociate into free charges (i.e., polarons). These charges result in a photocurrent ( I p ), while a small fraction populate trap states within the organic energy gap.…”
mentioning
confidence: 99%
See 1 more Smart Citation